2004
DOI: 10.1002/marc.200400165
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of Styrene in Cyclodextrin Channels: Can Confined Free‐Radical Polymerization Yield Stereoregular Polystyrene?

Abstract: Summary: Modeling of polystyrenes (PS) with various stereosequences in the narrow cylindrical channels corresponding to those found in γ‐cyclodextrin inclusion compounds (CD ICs) has been conducted. Based on the conformational modeling of stereoisomeric polystyrenes (PSs) in narrow channels, it was suggested that polystyrene with unusual microstructures might be produced by the constrained polymerization of styrene monomer in its γ‐CD‐IC crystals. The in‐situ polymerization of styrene inside the narrow channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 17 publications
2
30
0
Order By: Relevance
“…Thus, based on the modeling of stereoisomeric polystyrenes (PSs) in narrow g-CD channels, it was suggested [9], and confirmed here, that polystyrene with unusual microstructures might be produced via constrained polymerization of styrene monomer in its g-CD-IC crystals, as was described in a preliminary report [4]. Consequently, here we present the details of the polymerizations of styrene monomer in its channel structure inclusion compound formed with g-CD, as well as the characterization of the resulting PSs.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…Thus, based on the modeling of stereoisomeric polystyrenes (PSs) in narrow g-CD channels, it was suggested [9], and confirmed here, that polystyrene with unusual microstructures might be produced via constrained polymerization of styrene monomer in its g-CD-IC crystals, as was described in a preliminary report [4]. Consequently, here we present the details of the polymerizations of styrene monomer in its channel structure inclusion compound formed with g-CD, as well as the characterization of the resulting PSs.…”
Section: Introductionsupporting
confidence: 63%
“…1d). The first approach is a ''suspension'' method in which preformed [10] g-CD channel crystals containing only water of hydration are suspended into neat styrene to form the inclusion compound [4]. In the case of the suspension method, we have found that only the preformed g-CD channel crystals, and not as-received cage structure g-CD crystals, form styrene/g-CD channel -ICs when suspended in neat styrene.…”
Section: Formation Of Styrene/cyclodextrin Inclusion Compoundsmentioning
confidence: 97%
See 2 more Smart Citations
“…It was suggested that the probability of producing isotactic stereosequences, with narrower diameters, and syndiotactic stereosequences, with larger diameters, might be small. [9] Solution 13 C NMR observations suggested that a new type of PS with altered stereosequences could be obtained inside the g-CD CS channels only by suspension of styrene-g-CD CS -IC crystals in aqueous polymerization medium. [10,11] The first detailed attempts to obtain a highly stereoregular polyacrylonitrile (PAN) were made by White [3] in 1960 and employed the urea canal complex of AN.…”
Section: Full Papermentioning
confidence: 98%